EKSISTENSI ORGANISASI MASYARAKAT SIPIL DALAM DINAMIKA SISTEM DEMOKRASI DI INDONESIA - Pramestisari, Nyoman Ayu Sukma; Kebayantini, Ni Luh Nyoman (Universitas PGRI Sumatera Barat, 2022)
The history of the 1998 reformation has become a momentum for the implementation of Indonesian democracy after the authoritarian regime of the New Order Soeharto. Through a study of three major journals, it is seen how in Indonesia's democratic system it can be positively interpreted that mass organizations can grow. Even so, there are several actions of mass organizations that lead to the nuances of violence through their various actions. If using Marx's perspective, the state will regard this resistance as a threat to democracy. Another dimension is present when trying to understand that local mass organizations with violent radicals ideally have the aim of protecting local matters from being eroded by external interests that can threaten the identity and local community. Therefore, violence is understood as a way for them to defend and fight against things that are considered threatening. State recognition of locality- based identities and groups, including how mass organizations represent the existence of locality-based communities, is important. Recognition at this level should involve and pay attention to local wisdom so that policy as a product has authority in its application in the community.